Improved Detection of Multiple Faint Streak-like Space Targets from a Single Star Image - Yong Han; Desheng Wen; Jie Li; Zhangchi Qiao (Remote Sensing)
With the increasing number of human space activities, space surveillance systems need to be developed to reduce the risk of collisions between space assets and space debris. In this context, optical surveillance systems have gradually become a significant means of space surveillance due to their various advantages. Generally, the sidereal tracking mode is used to search for unknown moving targets, which appear as streaks in the star image generated by the optical surveillance system. Typical matched filtering can detect faint streak-like targets in star images, but it generates more false alarms and must traverse all potential filters. In this paper, the layering approach is used to improve the environment for detecting faint targets, in which dual-threshold segmentation is proposed to separate bright objects while maintaining the completeness of faint targets. Second, a streak-like matched filter unit and a dual-step search approach are recommended to lower the computational cost of matched filtering. Finally, perpendicular cross filtering is provided to further eliminate false positives. Experiments performed with both simulated and real data demonstrate that the proposed method has excellent detection performance for detecting multiple faint streak-like targets in a single star image.